2011
DOI: 10.1002/jso.21932
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with hepatocellular carcinoma after hepatic resection: Are elderly patients suitable for surgery?

Abstract: Careful follow-up and proper decision on hepatectomy upon assessment of PRS are important in elderly HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 45 publications
5
92
1
Order By: Relevance
“…Nanashima et al [38] showed that incidence of PHLF is not affected by age even though systemic complications are increased in elderly patients (≥70 years; 15 vs. 3%; p < 0.05). According to some authors, advanced age (≥70 years) increased the risk of postoperative morbidity and mortality with odds ratios of 1.02 (95% CI 1.01–1.03; p < 0.01) and 1.05 (95% CI 1.02–1.09; p < 0.01), respectively [13,16].…”
Section: Pathogenesismentioning
confidence: 99%
“…Nanashima et al [38] showed that incidence of PHLF is not affected by age even though systemic complications are increased in elderly patients (≥70 years; 15 vs. 3%; p < 0.05). According to some authors, advanced age (≥70 years) increased the risk of postoperative morbidity and mortality with odds ratios of 1.02 (95% CI 1.01–1.03; p < 0.01) and 1.05 (95% CI 1.02–1.09; p < 0.01), respectively [13,16].…”
Section: Pathogenesismentioning
confidence: 99%
“…As mentioned above, the posthepatectomy mortality reported in recent years varies between 0% and 5% and the onset of PHLF remains the main cause [10][11][12] . Factors that contribute to the onset of PHLF can be divided into three groups: patient-related factors (age, diabetes, obesity) [13,14] ; parenchyma-related factors (cirrhosis, cholestasis, steatosis, chemotherapy effects) [15][16][17] ; surgery-related factors (bleeding, ischemiareperfusion damage, sepsis, insufficient FLRV) [18][19][20][21] . With hepatic resection an amount of liver parenchyma is lost, and in the remnant hepatocytes arise both regeneration and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…This is highlighted by the even more controversial topic of hepatic resection for elderly patients with HCC. 20 This form of treatment should be reconsidered because over the last 20 years, there has been a continuous improvement in survival after HCC resection, even in older patients. 21 A tumor that is resectable must be present together with adequate functional liver reserve for sustaining life (found mostly in patients with Child-Pugh status A but sometimes in patients with Child-Pugh status B); this makes this treatment subset of elderly patients with HCC even smaller than the other subgroups.…”
Section: See Article On Page 423mentioning
confidence: 99%
“…22 There is evidence that this subgroup may be increasing in some countries. 20 The survival rates of elderly patients with HCC who are able to undergo surgical resection has been reported to be 58% at 3 years and 46% at 5 years. 20 Another study has reported similar survival rates after HCC resection in the elderly: 54.6% at 3 years and 43.2% at 5 years.…”
Section: See Article On Page 423mentioning
confidence: 99%
See 1 more Smart Citation